Impact of a planned dose interruption of dacomitinib in the treatment of advanced non-small-cell lung cancer (ARCHER 1042). (April 2017) - Kim, Dong-Wan; Garon, Edward B.; Jatoi, Aminah; Keefe, Dorothy M.; Lacouture, Mario E.; Sonis, Stephen; Gernhardt, Diana; Wang, Tao; Giri, Nagdeep; Doherty, Jim P.; Nadanaciva, Sashi; O'Connell, Joseph; et al.
Highlights: Dacomitinib is a pan-HER inhibitor in development for advanced NSCLC. Impact of a 4-day dacomitinib dose interruption on plasma exposure and adverse events (AEs) was examined in a phase II study. Plasma pharmacokinetic parameters of dacomitinib before dose interruption were comparable to that from other dacomitinib studies. Average median plasma dacomitinib concentration during dose interruption was ∼50% of median plasma Cmax before dose interruption. The toxicity profile was consistent with that from other dacomitinib studies. Abstract: Objectives: Dacomitinib is a pan-HER inhibitor for advanced non-small-cell lung cancer (NSCLC). We explored the impact of a planned 4-day dacomitinib dose interruption on plasma exposure of dacomitinib and adverse events (AEs) of interest in Cohort III of the ARCHER 1042 study. Materials and methods: Patients, treatment-naïve for advanced NSCLC with EGFR activating mutations, received oral dacomitinib 45 mg QD (once daily). A planned dose interruption occurred in Cycle 1 from Days 11 through 14. The primary endpoint was the pharmacokinetic (PK) characteristics of dacomitinib in Cycle 1 Day 10 and during dose interruption. Secondary endpoints included safety and concomitant medications used to treat AEs of interest. Results: Cohort III enrolled 25 patients. Median plasma Cmax of dacomitinib in Cycle 1 Day 10 was 83.40 ng/mL. Average median plasma dacomitinib concentration during the 4-day dose interruption was 42.63 ng/mL. In the first 8 weeks of treatment 1) 80% of patients used concomitant medications for dermatologic AEs, 76% for diarrhea, and 44% for stomatitis, and 2) all patients experienced treatment-emergent AEs and 28% had all-causality Grade 3 AEs. Conclusion: At 45 mg QD dosing, PK parameters of plasma dacomitinib in Cycle 1 Day 10 were comparable to that obtained in Cycle 1 Day 14 from other dacomitinib studies. Average median plasma dacomitinib concentration during the 4-day dose interruption was approximately half of the median plasma Cmax of dacomitinib observed prior to dose interruption. The toxicity profile was consistent with that from other studies of dacomitinib.